Fresno County Bar Association Annual Bar Banquet at TorNino's - Watkins, Howard::::::::: (1985)
1986 Fresno County Bar Association President Judy Soley presenting thank you gift to out-going 1985 Fresno County Bar Association President Donald Fischbach